2007
DOI: 10.1159/000109375
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Disturbance in the Auditory Cortex Related to a Low Serotonergic Neurotransmission in Women with Type 2 Diabetes

Abstract: Background/Aims: To determine if the slope of the amplitude/stimulus intensity function (ASF) of the N1/P2 component of the auditory evoked potential was increased in women with type 2 diabetes reflecting a low brain serotonergic activity in the auditory cortex. Methods: In a comparative study in women with type 2 diabetes and controls, we measured free, bound and total plasma L-tryptophan (L-Trp), neutral amino acids (NAA) and free fatty acids (FFA) and recorded the N1/P2 component of the auditory evoked pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 63 publications
(66 reference statements)
3
17
0
2
Order By: Relevance
“…These tests were undertaken as noninvasive clinical indicators of brain serotonin biosynthesis and activity. The present results confirm that FFT and FFT/total L-Trp ratio are significantly decreased in only diabetic patients (Herrera et al 2003;Manjarrez et al 2006Manjarrez et al , 2007. Interestingly, diabetic subjects who were depressed showed a similar decrease of these biochemical markers.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…These tests were undertaken as noninvasive clinical indicators of brain serotonin biosynthesis and activity. The present results confirm that FFT and FFT/total L-Trp ratio are significantly decreased in only diabetic patients (Herrera et al 2003;Manjarrez et al 2006Manjarrez et al , 2007. Interestingly, diabetic subjects who were depressed showed a similar decrease of these biochemical markers.…”
Section: Discussionsupporting
confidence: 88%
“…These findings support a lowered activity of serotonergic neurotransmission in the brain during the diabetic state, particularly in the auditory cortex (Manjarrez et al 2006(Manjarrez et al , 2007, which may be detected through a change in the amplitude of the N1/P2 component of the intensity-dependent auditory-evoked potentials (IDAEPs) (Hegerl and Juckel 1993;Manjarrez et al 2001Manjarrez et al , 2005aManjarrez et al ,b, 2006Manjarrez et al , 2007. We also recently observed in patients with type 1 and 2 diabetes a significant increase in the slope of the amplitude/stimulus intensity function (ASF slope) of the N1/P2 component, obtained at various intensities of auditory stimuli (Manjarrez et al 2006(Manjarrez et al , 2007. More specifically, a strong increase in auditory-evoked cortical responses with increasing stimuli intensities does reflect a low serotonergic activity, whereas low-intensity dependence is assumed to result from high serotonergic function, as we have observed in infants and rats with intrauterine growth restriction (Manjarrez et al 2001(Manjarrez et al , 2005a.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…The metabolites that were altered significantly were selected according to a variable VIP score of the (O)PLS model and the p values from t tests. These results revealed that 5 metabolites (azelaic acid, adipic acid, 5-hydroxyhexanoic acid, L-pyroglutamic acid, and D-norvaline) with a p value <0.05 and VIP ≥1, and L-tryptophan, which obviously varied in VIP although with p > 0.05, have a significant decrease in T2D patients [29] and play a role in the pathogenesis and development of diabetes, inflammatory diseases, and immunoregulation [30, 31]. They were selected as the best urine metabolites that differed significantly between the groups in this pilot study phase (Table 2).…”
Section: Resultsmentioning
confidence: 99%